Four new species of the lichen genus Diorygma (Graphidaceae, Ostropales) from Guizhou, China - Wei Wu; Shu-Hao Jiang; Lin-Shan Chai; He-Yun Bo; Ruvishika S. Jayawardena; Shao-Bin Fu; Qing-Feng Meng (MycoKeys)
Four new species of the lichen genus Diorygma from China are described based on morphological, chemical, and phylogenetic evidence. Phylogenetic analyses were conducted using both RAxML and Bayesian posterior probability inference, based on combined LSU and mtSSU sequences. The characteristic compounds were analyzed by colorimetric reactions and thin-layer chromatography. Diorygma guizhouense is characterized by small apothecia, a narrow to slightly open disc covered with white pruina, and the presence of stictic, salazinic, and norstictic acids. Diorygma leigongshanense is characterized by small, oval apothecia, a disc surrounded by entire, raised, and widely open thalline margins covered with thin, pale yellowish pruina, and the same chemical substances as D. guizhouense. Diorygma locitonitrus is distinguished by the presence of salazinic acid and hyaline, richly muriform ascospores, notably with distinctly smaller peripheral cells compared to the central cells. Diorygma weii is characterized by stellately branched apothecia with a closed to slit-like disc, a milky white thallus tinged with green, and the presence of only norstictic acid. Detailed morphological descriptions and illustrations of the new species are provided, along with a comprehensive species checklist highlighting the diagnostic characteristics of the known species in this genus.